Going outdoors: A natural antidote for attention fatigue?. (October 2017) - Merritt, Eileen G.
An emerging line of research suggests that a short walk in a natural setting may be the best way to restore students' flagging attention. To help students recover from the inevitable fatigue that accompanies the deep attention expected in schools, educators have always built some breaks into the schedule. Now, researchers are suggesting that students may benefit most when those breaks include being allowed to take walks in natural settings, play in nature, study outdoors, and often by simply being close to vegetation during the school day. Around the world, educators are experimenting with new school designs that put natural features in the foreground .